Analisis Pekerjaan Beton Bertulang dengan Building Information Modelling (BIM) 5D pada Proyek Pembangunan Kantor dan Pos Jaga Depot Supply Point Pertamina Lubricants Tarakan - Putra, Zam Zam Dade; Danuarta, Fachry; Pratiwi, Reno; Hendriyani, Irna (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
The calculation of the cost budget by consultants mostly uses Microsoft Excel. This causes opportunities for errors due to inaccuracies in interpretation and calculation in elaborating the complexity of the building to be built. Calculations that still use excel in development projects where it can result in a much larger calculation difference resulting in cost overruns. For this reason, it is necessary to require more effective cost estimation planning. One of the latest project management information systems today is Building Information Modeling (BIM). BIM has great potential to share visualize information, visualize construction progress, provide information quickly. Therefore, this research uses BIM 5D (Autodesk Revit software) which functions to estimate the cost budget of a project. The Plan Budget Cost (RAB) figure will not be 100% accurate. The purpose of this study is to determine the comparison and difference in volume calculations and RAB using BIM 5D dimensions with calculations of Planning Consultants on Reinforced Concrete Works in the Office and Post Security Depot Supply Point Pertamina Lubricants Tarakan Construction Project. The results of the calculation with BIM 5D method and the Planner Consultant obtained the results of the calculation of the difference where the comparison of the volume of reinforcement is a difference of 3.83% while in concrete work the difference is 4.37%. Meanwhile, the results of the RAB calculation on reinforced concrete work cost difference of 4.10%.